Efficacy of 0.5 mg/kg of propofol at the end of anesthesia to reduce the incidence of emergence agitation in children undergoing general anesthesia with sevoflurane - Andi Ade Wijaya Ramlan; Dimas K. Bonardo Pardede; Arif H. M. S Marsaban; Jefferson Hidayat; Fildza Sasri Peddyandhari (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Emergence agitation (EA) is a common transient behavioral disturbance after inhalational anesthesia and may cause harm to the patient. This study evaluated the efficacy of 0.5 mg/kg of propofol administered at the end of anesthesia to reduce the incidence of EA in children undergoing general inhalational anesthesia. Material and Methods: This double-blind randomized clinical trial was done in children aged 1-5 years undergoing general anesthesia with sevoflurane. One hundred and eight subjects were included using consecutive sampling method and randomized into two equal groups. Propofol in the dose of 0.5 mg/kg was administered at the end of anesthesia to children in the propofol group, while those in the control group did not receive any intervention at the end of anesthesia. Incidence of EA, transfer time, postoperative hypotension, desaturation, and nausea-vomiting were observed. Aono and Pediatric Anesthesia Emergence Delirium scale were used to assess EA. Results: Incidence of EA was 25.9% in the propofol group compared to 51.9% in the control group (RR = 0.500; 95% CI 0.298-0.840; P = 0.006). Mean transfer time in propofol group was longer (9.5 ± 3.9 min) than control group (7.8 ± 3.6 min) (mean difference 1.71 min; 95% CI 0.28-3.14; P = 0.020). Hypotension was found in one patient (1.9%) in propofol group, while in control group there was none. Nausea-vomiting was found in five patients (9.3%) in propofol group and eight patients (14.8%) in control. There was no desaturation in both the groups. Conclusion: Administration of 0.5 mg/kg of propofol at the end of anesthesia effectively reduces the incidence of EA in children undergoing general inhalational anesthesia with sevoflurane.